DEBUS DI BANTEN; PERTAUTAN TAREKAT DENGAN BUDAYA LOKAL - MOH. HUDAERI (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Debus is one of noticeable appearance of the relationship between local tradition of Banten and Islam (mystical brotherhood). This relationship causes not only the conformity but also the dispute and controversy among the community. In debus, there are not only traditions derived from tarekat (mystical brotherhood) such as wirid, tawasul and bai'at, but also jangjawokan (local languages) and the traditional defense art. Studying debus not only observes the development of this art in Bantenese society, but also describes the anthropological condition of Islamic tradition In Banten. It indicates that the Islamic tradition of Bantenese society is more sufistic. It is probabfy because of the equality and the effinity between Islam and the mystical condition of local society of Banten. This article will discuss how is the development of debus in Bantenese society? What sources are used as references in debus performance? How does the anthropological perspective view the practice of debus performance in the context of Islamic culture in the Archipelago? Keywords: Debus, Islam Banten, Wirid, Jangjawokan.